The Geriatric Hearcare Services as an example of integrated ‘pathway’ in case- and care management - Lerch, Michael (Igitur, Utrecht Publishing & Archiving, 2009)
PURPOSE: Initiation of an multimodal, customer focused service network across the service sectors for multimorbid patients: for example the hard-of-hearing. CONTEXT: The lack in accessibility of services, flexibility of appointments and handicap-oriented communication skills often prevents the geriatric patient from partaking in the medical services offered. The geriatric hearcare service and its care for the hard-of-hearing outlines the possibilities of an integrated, multimodal setting at all levels of care for these patients. DATA SOURCE: The scientific evaluation of >2000 hard-of-hearing patients in geriatric care from 2002 to 2008. CASE DESCRIPTION: Upon standardized admission patients are screened for a history in hard-of-hearing. Organised and accompanied by a specially trained hearcare-nurse, a patient with a possible auditive decline is then seen by an ENT and hearing-aid technician for examination and audiometry. The patient is then seen by an neuropsychologist for a cognitive evaluation. After these tests, documented by the hearcare-nurse, the patient and his next-of-kin are informed of the outcome, the treatment options and follow-up in the out-patient setting. CONCLUSION AND DISCUSSION: The integration of services across sectors of care and the provided co-ordination leads to a higher degree of customer satisfaction, a lesser rate of cases of hard-of-hearing missed and better continuity in care on a long-term basis.